2022-RA-1028-ESGO Role of radiotherapy in platinum sensitive oligometastatic recurrent ovarian cancer: a valid alternative to delay systemic treatment. (20th October 2022) - Bonaldo, Giulio; Lazzari, Roberta; Durante, Stefano; Corrao, Giulia; Lapresa, Mariateresa; Parma, Gabriella; Achilarre, Maria Teresa; Aloisi, Alessia; Betella, Ilaria; Garbi, Annalisa; de Vitis, Luigi Antonio; Schivardi, Gabriella; et al.
Abstract : Introduction/Background: Ovarian cancer (OC) represents the most lethal gynaecological malignancy, with approximately 80% of advanced OC patients experiencing a recurrence after primary treatment. The role of radiotherapy in recurrent OC has been recently explored. The aim of this study was to assess the efficacy of advanced radiotherapy at the time of the 1st platinum-sensitive oligometastatic recurrence. Methodology: Patients with epithelial OC undergoing primary treatment at the European Institute of Oncology, Milan, from January 2010 to April 2019 were retrospectively identified. Among those, patients treated with stereotactic or intensity-modulated radiotherapy (IMRT) alone at the time of 1st platinum-sensitive oligometastatic recurrence were included. Patients with encephalic or vertebral recurrence were excluded. Response rate (based on RECIST 1.1 criteria), predictor of treatment response, and survival outcome were evaluated with appropriate statistical analysis. Results: In total, 31 patients meeting inclusion criteria were included. Of them, 18(58, 1%) had a complete response, 7(22, 6%) a partial response, and 6 (19.3%) a progressive disease [1(3.2%) both in-field and out-of-field, 5(16.1%) out-of-field]. Among them, 30(96.8%) had a subsequent relapse, of which 22(73.3%) were treated with chemotherapy while the remaining 8(26.7%) underwent further radiotherapy or thermoablation. The median interval between radiotherapy and the subsequent recurrence requiring chemotherapy was 16 months (range 4–126), with 18(58.1%) patients having a subsequent recurrence requiring chemotherapy after 12 months or more. Upon univariate analysis, median platinum-free interval before radiotherapy in patients with complete/partial response was longer than in patients with progressive disease (23 vs. 11 months, p=0.06), although the association did not meet the conventional level of statistical significance. Conclusion: In our experience, radiotherapy alone represents a valuable option in the treatment of 1st oligometastatic platinum-sensitive recurrent epithelial OC, providing a good response rate and allowing to extend the platinum-free interval. Further studies are required to confirm our results and identify predictors of treatment response.